2017
DOI: 10.1002/ajmg.b.32581
|View full text |Cite
|
Sign up to set email alerts
|

A polygenic risk score analysis of psychosis endophenotypes across brain functional, structural, and cognitive domains

Abstract: This large multi‐center study investigates the relationships between genetic risk for schizophrenia and bipolar disorder, and multi‐modal endophenotypes for psychosis. The sample included 4,242 individuals; 1,087 patients with psychosis, 822 unaffected first‐degree relatives of patients, and 2,333 controls. Endophenotypes included the P300 event‐related potential (N = 515), lateral ventricular volume (N = 798), and the cognitive measures block design (N = 3,089), digit span (N = 1,437), and the Ray Auditory Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 150 publications
(172 reference statements)
2
39
0
Order By: Relevance
“…Since attention is strongly impaired in individuals with SZ, most studies considered this domain in their analyses. Significant associations between SZ-PRS and attention are only reported by Nakahara et al [27] , while other studies did not reveal any significant association between SZ-PRS and attention [28,33] . Post hoc analysis by Xavier et al [35] revealed a significant association between SZ-PRS and vigilance but the finding did not survive correction for multiple testing.…”
Section: Attention/vigilancementioning
confidence: 90%
See 3 more Smart Citations
“…Since attention is strongly impaired in individuals with SZ, most studies considered this domain in their analyses. Significant associations between SZ-PRS and attention are only reported by Nakahara et al [27] , while other studies did not reveal any significant association between SZ-PRS and attention [28,33] . Post hoc analysis by Xavier et al [35] revealed a significant association between SZ-PRS and vigilance but the finding did not survive correction for multiple testing.…”
Section: Attention/vigilancementioning
confidence: 90%
“…While the studies of Ranlund and Whalley [28,34] were not able to find any association between SZ-PRS and verbal learning, Nakahara et al [27] showed a significant association between verbal learning and SZ-PRS. Also, in this case the post hoc analysis by Xavier et al [35] on a possible association between SZ-PRS and memory did not survive correction for multiple testing.…”
Section: Verbal Learning and Memorymentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, the PRS provides a continuous, quantitative measure of an individual's overall genetic burden that can be associated with pathophysiological measures, such as gene/protein expression and brain activity/connectivity. For instance, PRSs have been recently associated with functional/structural brain imaging measures as well as cognitive performance in psychosis (Ranlund et al 2018). Likewise, the quantification of PRSs coupled with intermediate pathophysiological mediators can facilitate the translation of genetic findings into biological insights.…”
Section: Translating Genetic Findings Into Disease Mechanismsmentioning
confidence: 99%